Vildagliptin: optimal control in type 2 diabetes mellitus treatment - Alexander Sergeevich Ametov (Endocrinology Research Centre, 2015)
Incretin hormones are important for normal pancreatic islet function and glucose homeostasis. Sensitivity to glucose of the α- and β-cells of the pancreas is diminished in type 2 diabetes mellitus (T2DM), leading to impaired insulin secretion, insulin resistance due to elevated glucagon levels in hyperglycaemia and impaired glucagon counterregulation in hypoglycaemia. In addition, T2DM is associated with increased lipotoxicity-induced insulin resistance. This article is a comprehensive review of the safety and efficacy of vildagliptin in patients with T2DM and evaluates the extra-pancreatic effects of incretin-based therapies. Clinical evidence has proven that vildagliptin effectively decreases HbA1c with a low risk of hypoglycaemia and is weight neutral. Vildagliptin also suppresses postprandial triglyceride (TG)-rich lipoprotein levels after ingestion of fat-rich meals and reduces fasting lipolysis, suggesting inhibition of fat absorption and reduced TG stores in non-fat tissues.